Study guides

☆☆

Q: 6x plus 12 equals -78-9x

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

(9,6)

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

In 6x + 4 = 12, x = 4/3

6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...

3x+42=6x+12 42=6x-3x+12 42=3x+12 42-12=3x 30=3x 10=x

Related questions

(9,6)

6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2

In 6x + 4 = 12, x = 4/3

6x+4=3x+12 => 6x-3x=12-4 => 3x=8 => x=8/3=2.666...

x would be -3

3x+42=6x+12 42=6x-3x+12 42=3x+12 42-12=3x 30=3x 10=x

4x + 6 = 6x - 12-4x -4x6 = 2x - 12+12 +1218 = 2xx=9

6x + 47 = 9x + 11 6x + 36 = 9x 36 = 3x 12 = x

If: x+3+6x+9 = 0 then 7x+12 = 0 So: 7x = -12 and x = -12/7

perpendicular

30 - 12 = 18

x2 + 6x + 9 = 81 x2 + 6x = 72 x2 + 6x - 72 = 0 (x+12)(x-6) = 0 x= -12, 6 (two solutions)